„Siedem ksiąg” żywieckiego cechu krawieckiego z 1745 roku - Jarosław Dusik (In Gremium. Studies in History, Culture and Politics, 2024)
Żywiec was founded at the turn of the 13th and 14th centuries. As the only urban center in the area, it had a well-developed craft guild system. One of the oldest guilds in Żywiec was the tailors' guild, which, for over 100 years (1580-1699), formed a joint association with furriers. After its dissolution, the tailors began to strengthen their independent image. A clear manifestation of these efforts was the formulation of strict rules for advancement in their guild, contained in the so-called "seven books" in the tailors' guild book from 1745. These regulations governed the attainment of up to seven stages in the guild career, namely learning the trade, liberation from it, wandering, becoming a younger brother/master, middle master, senior master, and finally, the guild master. Therefore, these "seven books" serve as an example of comprehensive development by guild legislation of the issue of guild careers, a form of regulation rarely encountered in this manner.